On Novel Non-Organometallic Aryl Nucleophile in Palladium-Catalyzed Arylation - Didier Villemin; Arnaud Jullien; Nathalie Bar (Chemistry Proceedings)
Phenylazocarboxylate is described as a novel non-organometallic aryl nucleophile in palladium-catalyzed arylation.